Establishment of a Special Education School for Women - Ahmad Nur Ihsan Purwanto; Lia Siti Julaeha; Widya Nur Fauziyah; Dhelia Aprina Pradistya; Hilda Ziradine Syahrani; Indriyana Eka Salsabila; Jihan Salsabila; Alfian Airlangga Asis (SocietalServe: Journal of Community Engagement and Services, 2024)
This study explores the establishment of a specialized educational institution, The House of Humaira, aimed at empowering young Muslim women through a blend of homeschooling and boarding school methods. Located in Purwakarta, this initiative addresses the significant issue of gender disparities in education by providing a model that integrates Islamic principles with academic and cognitive development. Through targeted social outreach, financial planning, and operational management, the project enhances awareness of the importance of education for women, emphasizing their roles as future mothers and contributors to societal growth. By creating tailored educational programs and sustainable management systems, the initiative seeks to produce competent, productive, and cooperative young women, serving as a blueprint for similar institutions nationwide. Key outcomes include an operational framework, a financial planning template, and community engagement through digital platforms. This project underscores the critical role of education in fostering self-reliance and leadership among women, ensuring long-term societal impact.